Antimicrobial resistance profiles and genetic basis of resistance among non-fastidious Gram-negative bacteria recovered from ready-to-eat foods in Kibera informal housing in Nairobi, Kenya. Issue 6 (11th June 2021) - Maina, John; Ndung'u, Perpetual; Muigai, Anne; Kiiru, John
Abstract : Objective. This cross-sectional study conducted in Kibera, Kenya, sought to gain insights on relative microbial contamination levels of popular unprocessed food types, determine antimicrobial resistance (AMR) burden and the carriage of integrons that are essential elements for spreading antimicrobial resistance genes (ARG). Foods analysed consisted of cooked vegetables (kale, cabbage, and nightshades), boiled cereal foods (beans, rice, and Githeri, which is a mixture of beans and maize), meat, Omena fish (fried silver cyprinids), and Ugali (a product of simmered maize flour in boiled water). Results. The analysis detected contamination levels exceeding 2×10 4  c.f.u. ml −1 in 106 (38 %) of the 281 ready-to-eat foods analysed. The majority of food types had microbial contaminations of between 4.0×10 4  and 2.3×10 6  c.f.u. ml −1 . Kale was the most contaminated with a mean of 2.3×10 6  c.f.u. ml −1, while Omena was the least contaminated with 4.0×10 4  c.f.u. ml −1 . Foods sold close to open sewage and refuse sites were more contaminated than those sold in relatively 'cleaner' settings ( P <0.0001, O.R 0.1162, C.I 0.1162–0.120). A total of 405 bacterial isolates were recovered and included; Klebsiella spp 116 (29 %), Escherichia coli 104 (26 %), Enterobacter agglomerans 88 (22 %), Proteus mirabilis 30 (7 %), Salmonella spp 28 (7 %), Citrobacter freundii 27 (7 %) and Serratia marcescens 12 (3 %). Imipenem (IPM, 100 %) was the most effective antimicrobial agent, followed by cefepime (98 %). Ampicillin (AMP, 33 %), trimethoprim (TMP, 27 %), and sulfamethoxazole (SMX, 23 %) on the other hand, were the least effective antimicrobials. The analysis also found ten isolates (2 %) that had co-resistance to third-generation cephalosporins, fluoroquinolone (CIP), quinolones (NAL) and aminoglycosides (GEN); hereby we refer to this phenotype as the βFQA. The prevalence of multidrug-resistant (MDR) strains was 23 % (93), while that of extended-spectrum β-lactamases (ESBL) producing strains was 4 % (17). The bla TEM was the most prevalent (55 %) β-lactamase ( bla ) gene among the screened 93 MDR-strains. Carriage of class one integrons ( intI 1) was more common (23 %) than intl 2 (3 %) among these MDR-strains. Bacterial diversity analysis using the GTG5 -PCR found no significant clusters for analysed E. coli and K. pneumoniae, suggesting recovered isolates were genetically diverse and not due to non-clonal expansion. The findings of this study are an indication that contaminated foods can be a reservoir for enteric pathogens and a source of AMR strains.